SEMANTIK LEKSIKAL PADA LIRIK LAGU ALBUM SEMOGA SEMBUH KARYA IDGITAF - Uliana Hidayatika; Difa Aprilia; Neneng Nurjanah (Universitas Hamzanwadi, 2025)
This research is motivated by the popularity of sad songs. One of the famous albums that contains songs with sad nuances is the mini album Semoga Sembuh by Idgitaf. The researcher wants to draw meaning relations from lexical semantics that are paradigmatic in the lyrics of the mini album songs. Descriptive qualitative is used as a method by researchers in this article. The song lyrics on the mini album Semoga Sembuh are used as the data source. The results of this study found the existence of meaning relations that contain sadness and fear of the singer conveyed in the form of sung words. The meaning relation is drawn from the paradigmatic lexical semantic findings in the data source. Repetition is found 54 times (41%) which reinforces the feelings of the songwriter. Synonymy is found 20 times (15%) which on average is sadness and difficulty. Then antonymy is found 20 times (15%) which expresses the difference in feelings or conditions between happy times and sad times. Then hyponyms were found 36 times (27%), and hypernyms were found 2 times (2%), namely sadness and fear. Every meaning relation found can be used as a lesson in everyday life, especially for gen z to survive, always be strong, and be honest with one's own feelings in living life, especially in difficult times.